2021
DOI: 10.1093/pm/pnaa402
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Preoperative Pain, Conditioned Pain Modulation, and Pain Catastrophizing Predicts Postoperative Pain 12 Months After Total Knee Arthroplasty

Abstract: Objectives Approximately 20% of knee osteoarthritis patients undergoing total knee arthroplasty (TKA) report chronic postoperative pain. Studies suggest that preoperative variables such as impaired descending pain control, catastrophizing, function, and neuropathic pain–like symptoms may predict postoperative pain 12 months after TKA, but the combined prediction value of these factors has not been tested. The current prospective cohort study aimed to combine preoperative risk factors to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 55 publications
4
77
0
2
Order By: Relevance
“…Similar to previous studies [42,43], our study found that patients with stronger pain intensity during activity were more likely to experience pain catastrophizing. The result was consistent with a recent study by Larsen et al [44], and authors also pointed out preoperative clinical pain intensity, high levels of pain catastrophizing thoughts, and impaired conditioned pain modulation may predict long-term postoperative pain 12 months after TKA. A review by Quartana et al indicated [45] a relationship of catastrophizing and pain intensity.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous studies [42,43], our study found that patients with stronger pain intensity during activity were more likely to experience pain catastrophizing. The result was consistent with a recent study by Larsen et al [44], and authors also pointed out preoperative clinical pain intensity, high levels of pain catastrophizing thoughts, and impaired conditioned pain modulation may predict long-term postoperative pain 12 months after TKA. A review by Quartana et al indicated [45] a relationship of catastrophizing and pain intensity.…”
Section: Discussionsupporting
confidence: 92%
“…It is also important to highlight that there are other factors, such as pain catastrophising, that interact with central sensiti sation to determine whether a postoperative outcome is positive or not. 80 Also, the presence of central sensitisation should not prevent healthcare providers from searching for and possibly treating peripheral dysfunctions, in the context of a multifactorial disease model that considers both peripheral and central components. Unfortunately, many clinicians globally continue to focus on treating only peripheral drivers of central sensitisation, rather than adhering to a multifactorial disease model.…”
Section: Can Central Sensitisation Be Treated In Patients With Chronimentioning
confidence: 99%
“…TSP has also been found to be a predictor of limited analgesic effect of non-steroidal anti-inflammatory drugs (NSAIDs) [ 46 ] in OA. CPM is a proxy for descending pain inhibitory control [ 60 ], is impaired in severe patients with OA [ 6 ] and impaired CPM has been associated with higher levels chronic postoperative pain [ 34 , 57 ] and poor analgesic effects to NSAIDs effects in patients with OA [ 21 , 48 ].…”
Section: Introductionmentioning
confidence: 99%